My Boss My Hero: Increasing Responsibility Using Educational Cinema - Irchamna Chamalia; Roko Patria Jati (Pamomong: Journal of Islamic Educational Counseling, 2022)
Students need to have a good responsibility at school to keep up with all academic demands set by teachers and schools. Ironically, some students still exhibit low responsibility awareness. This research aims to determine the effectiveness of group guidance services through educational cinema in increasing student responsibility. Quantitative research with a one-group pretest-posttest design was used. The subjects of this study were eight 11th-grade vocational high school students. The data were collected using a responsibility scale and analyzed using non-parametric statistics, i.e., the Wilcoxon test. The results of the analysis show that the count Z value is greater than the table Z (2.5271.96) with a significance value of 0.012 (0.05), meaning that group guidance services through educational cinema effectively increase students’ responsibility. This research proposes an alternative to group guidance services that are creative, interesting, and fun based on educational cinema to increase student responsibility.